The Linguistic Features in Egyptian-Authored English Research Article Literature Reviews in Linguistics - Rabie, Hend; Boraie, Deena (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
The current study aims at investigating and comparing the linguistic features of lexical items, tense usage, and voice choice in a sample of ten Egyptian-authored linguistics research article (RA) literature reviews (LRs) in local and international English-medium journals between 2013 and 2019. The paper followed a combination of genre-based and corpus-driven approaches, analyzing the data qualitatively and quantitatively. It adopted the state-of-the-art #LancsBox. The analysis revealed interesting differences between both sub-corpora in the use of lexis, especially in Moves 2 and 3. It was found that lexis varied to reflect the different rhetorical functions of the LR. They also differed in the use of the past simple tense. However, both sub-corpora agreed on using the present simple tense and active voice the most. This paper contributes to the literature by providing a helpful guide for Egyptian and novice researchers to use the linguistic features more appropriately in their LRs. It has pedagogical implications for designing EAP and ESP courses. Further studies on larger corpora are needed to analyze the linguistic features and highlight variations across genres, disciplines, and languages.